Aging and anatomical variations in lung tissue stiffness - Sicard, Delphine (Am J Physiol Lung Cell Mol Physiol, 2018)
Lung function is inherently mechanical in nature and depends on the capacity to conduct air and blood to and from the gas exchange regions. Variations in the elastic properties of the human lung across anatomical compartments and with aging are likely important determinants of lung function but remain relatively poorly characterized. Here we applied atomic force microscopy microindentation to characterize human lung tissue from subjects ranging in age from 11 to 60 yr old. We observed striking anatomical variations in elastic modulus, with the airways (200- to 350-µm diameter) the stiffest and the parenchymal regions the most compliant. Vessels (diameter < 100 µm) represented an intermediate mechanical environment and displayed diameter-dependent trends in elastic modulus. Binning our samples into younger (11–30 yr old) and older (41–60 yr old) groups, we observed significant age-related increases in stiffness in parenchymal and vessel compartments, with the most pronounced changes in the vessels. To investigate cellular mechanisms that might contribute to vascular stiffening with aging, we studied primary human pulmonary artery smooth muscle cells from subjects ranging in age from 11 to 60 yr old. While we observed no change in the mechanical properties of the cells themselves, we did observe trends toward increases in traction forces and extracellular matrix deposition with aging. These results demonstrate age-related changes in tissue mechanical properties that likely contribute to impaired lung function with aging and underscore the potential to identify mechanisms that contribute to mechanical tissue remodeling through the study of human cells and tissues from across the aging spectrum.